2021
DOI: 10.1177/10499091211011145
|View full text |Cite
|
Sign up to set email alerts
|

Examining Barriers and Facilitators to Palliative Care Access in Rural Areas: A Scoping Review

Abstract: Background: Despite the growth of palliative care (PC), access to PC remains challenging for rural Americans living with chronic diseases. Given the demand and benefits of PC, a comprehensive view of PC access would inform policymakers in developing PC services in rural areas. Objective: This scoping review aimed to understand the barriers and facilitators to PC access in rural areas from the voices of service users and service providers during the past decade. Methods: A scoping literature review was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 42 publications
(167 reference statements)
0
12
0
Order By: Relevance
“…Rural communities have limited access to medical specialist services. Depending on the size of the community, there may be limited health infrastructure, limiting acute and chronic medical care for the diagnosis and management of complex diseases [ 7 ]. Rural older Australians experience higher rates of complex multimorbid health conditions than their urban counterparts [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rural communities have limited access to medical specialist services. Depending on the size of the community, there may be limited health infrastructure, limiting acute and chronic medical care for the diagnosis and management of complex diseases [ 7 ]. Rural older Australians experience higher rates of complex multimorbid health conditions than their urban counterparts [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 A recent scoping review showed that most rural areas in the United States have limited access and provision of PC services because of lack of awareness, accessibility issues such as transportation or weather, shortage of trained staff, and limited funding and resources. 3 Consequently, rural communities are more vulnerable to PC disparities in the management of chronic illness than their urban counterparts. 6 As aforementioned, the pandemic-imposed restrictions have further intensified such inequities and require immediate attention toward the provision of accessible and adequate PC services in rural communities.…”
Section: Introductionmentioning
confidence: 99%
“…2 Especially in small towns and rural communities, PC faced additional constraints due to limited funding support, resources, and facilities, resulting in the discontinuation of or inadequate PC services for patients and families in rural clinics and hospitals. 3 Rural communities demonstrate unique needs, attitudes, and behaviors toward health and illness. Individuals with advanced chronic illnesses have complex physical, psychological, social, and existential needs 4 and therefore require integrated PC services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations